2021
DOI: 10.1016/j.psyneuen.2020.105084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gender and personality on everyday moral decision-making after acute stress exposure

Abstract: developed the study concept and study design. Nina Singer performed data collection. Nina Singer and Ludwig Kreuzpointner performed data analysis. Nina Singer drafted the manuscript under the supervision of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 171 publications
(575 reference statements)
4
23
0
Order By: Relevance
“…In humans, inconsistent data are reported in the literature about sex differences in cortisol levels, probably because of the difficulty to measure cortisol in controlled conditions. For example, females were found to have higher free cortisol levels than males, as in rodents, in one study with 1258 participants [ 37 ] but the opposite was found in another one where there was no differences at rest and a higher response after a social stress in men [ 38 ]. A meta-analysis for post-stress cortisol levels concluded that men had higher cortisol levels than women but the sex differences could be explained by variations in methodologies [ 39 ].…”
Section: Sex Dimorphism Related To Gonadal Hormones Across Developmentioning
confidence: 99%
“…In humans, inconsistent data are reported in the literature about sex differences in cortisol levels, probably because of the difficulty to measure cortisol in controlled conditions. For example, females were found to have higher free cortisol levels than males, as in rodents, in one study with 1258 participants [ 37 ] but the opposite was found in another one where there was no differences at rest and a higher response after a social stress in men [ 38 ]. A meta-analysis for post-stress cortisol levels concluded that men had higher cortisol levels than women but the sex differences could be explained by variations in methodologies [ 39 ].…”
Section: Sex Dimorphism Related To Gonadal Hormones Across Developmentioning
confidence: 99%
“…In two mixed-sample studies, results showed that the increase in CORT levels under stress was weakly/moderately associated with a decrease in altruistic [ 38 ] and utilitarian [ 39 ] judgments only in the face of dilemmas with specific characteristics (everyday moral dilemmas/high emotional dilemmas and sacrificial moral dilemmas/personal dilemmas, respectively). In three other studies, led by the same group of researchers, and using everyday moral dilemmas [ 31 , 40 , 41 ], the results had a different direction, as an increase in altruistic responses was observed under stress, which was not always associated with CORT levels. The first association found was expressive for the male sample (r = 0.35) [ 31 ], whereas, in the second study [ 41 ], it was only meaningful for the female sample (r = 0.34).…”
Section: Resultsmentioning
confidence: 96%
“…In three other studies, led by the same group of researchers, and using everyday moral dilemmas [ 31 , 40 , 41 ], the results had a different direction, as an increase in altruistic responses was observed under stress, which was not always associated with CORT levels. The first association found was expressive for the male sample (r = 0.35) [ 31 ], whereas, in the second study [ 41 ], it was only meaningful for the female sample (r = 0.34). In the third study [ 40 ], there were no significant correlations in an exclusively male sample.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations